IMMU-45. COMBINATION OF EGFRVIII CAR T-CELL THERAPY AND PARACRINE GAM MODULATION FOR THE TREATMENT OF GBM. (12th November 2021) - Martins, Tomás A; Ritz, Marie-Françoise; Shekarian, Tala; Schmassmann, Philip; Kaymak, Deniz; Bicvic, Valentina; Hutter, Gregor
Abstract: The GBM immune tumor microenvironment mainly consists of protumoral glioma-associated microglia and macrophages (GAMs). We have previously shown that blockade of CD47, a 'don't eat me'-signal overexpressed by GBM cells, rescued GAMs' phagocytic function in mice. However, monotherapy with CD47 blockade has been ineffective in treating human solid tumors to date. Thus, we propose a combinatorial approach of local CAR T cell therapy with paracrine GAM modulation for a synergistic elimination of GBM. We generated humanized EGFRvIII CAR T-cells by lentiviral transduction of healthy donor human T-cells and engineered them to constitutively release a soluble SIRPγ-related protein (SGRP) with high affinity towards CD47. Tumor viability and CAR T-cell proliferation were assessed by timelapse imaging analysis in co-cultures with endogenous EGFRvIII-expressing BS153 cells. Tumor-induced CAR T-cell activation and degranulation were confirmed by flow cytometry. CAR T-cell secretomes were analyzed by liquid chromatography-mass spectrometry. Immunocompromised mice were orthotopically implanted with EGFRvIII + BS153 cells and treated intratumorally with a single CAR T-cell injection. EGFRvIII and EGFRvIII-SGRP CAR T-cells killed tumor cells in a dose-dependent manner (72h-timepoint; complete cytotoxicity at effector-target ratio 1:1) compared to CD19 controls. CAR T-cells proliferated and specifically co-expressed CD25 and CD107a in the presence of tumor antigen (24h-timepoint; EGFRvIII: 59.3±3.00%, EGFRvIII-SGRP: 52.6±1.42%, CD19: 0.1±0.07%). Differential expression analysis of CAR T-cell secretomes identified SGRP from EGFRvIII-SGRP CAR T-cell supernatants (-Log10 qValue /Log2 fold-change = 3.84/6.15). Consistent with studies of systemic EGFRvIII CAR T-cell therapy, our data suggest that intratumoral EGFRvIII CAR T-cells were insufficient to eliminate BS153 tumors with homogeneous EGFRvIII expression in mice (Overall survival; EGFRvIII-treated: 20%, CD19-treated: 0%, n= 5 per group). Our current work focuses on the functional characterization of SGRP binding, SGRP-mediated phagocytosis, and on the development of a translational preclinical model of heterogeneous EGFRvIII expression to investigate an additive effect of CAR T-cell therapy and GAM modulation.